COMPARATIVE EFFECTIVENESS OF VARIOUS FERTILIZERS IN CONTROLLING ROOT KNOT NEMATODE INFECTION IN OKRA (Abelmoschus esculentus) IN MAKURDI, BENUE STATE - Olusesan, Adepoju Isaiah; Ene, Danladi Mary (Program Studi Agroteknologi Universitas Siliwangi, 2024)
Root knot nematode infection poses a serious threat to Okra cultivation in Nigeria. A field research was conducted at the Teaching and Research Farm of the Federal University of Agriculture, Makurdi, Benue State to offer valuable insights into combating root-knot nematode infections on okra using different fertilizer types. The experiment was designed using a factorial design with three (3) varieties of okra and two fertilizer treatments at different intervals. The seeds were planted two (2) seeds per hole on a spacing of 50cm after which normal agronomic practices were carried out on nematode infested soil. The results indicate that both SuperGro liquid fertilizer and Geese dung have potential in suppressing root-knot nematode infections on okra. Specifically, the application of Geese dung at either 2 or 4 weeks interval demonstrated a notable reduction in root gall index (RGI), suggesting its effectiveness in mitigating nematode damage. Furthermore, the application of Geese dung led to improved yield, manifested through increased fruit size and quantity. However, it's crucial to note that the application of SuperGro fertilizer at a 4-week interval resulted in a significantly higher Root Gall Index (RGI) compared to other treatments. The research highlights the potential of organic fertilizers like Geese dung as a sustainable and effective means of nematode control in okra cultivation. Nonetheless, future studies are warranted to identify the active ingredients in Geese dung responsible for nematode suppression, which could provide valuable insights for refining treatment protocols and enhancing agricultural practices.